Preferences for Sustainable Agriculture Attributes and Technical Efficiency among Family Maize Farmers in Lufwanyama District, Zambia - Mungatana, Eric D. (University of Pretoria, 2020)
Thesis (MPhil (Agricultural Economics))--University of Pretoria, 2020